On the Decriminalization of Sex Work in China HIV and Patients' Rights - Meng, Jinmei; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This study argues that the decriminalization of sex work can be a potential national strategy for China to promote its human rights and contain the spread of HIV.
Keywords: Science; Science; Science, general